Estimates for two-phase nonlinear conductors via iterated homogenization - Idiart, Martín Ignacio (2013)
Estimates for the overall response of two-phase nonlinear conductors are derived via an iterated homogenization approach. The approach consists in the construction of sequentially laminated microgeometries for which the overall response can be determined exactly. The estimate depends on the one- and two-point microstructural correlations through the volume fractions of each constituent phase and the H-measures of the microstructure. Sample results for power-law random conductors are provided and compared with earlier predictions. The work concludes with a discussion on the possible extremal character of sequential laminates.